Measuring Rural Teachers' Digital Competence to Communicate with the Educational Community - Guillén-Gámez, Francisco David; Mayorga-Fernández, María Josefa (Springer Nature, 2022)
Teachers’ communication with the educational community (students, families and teachers) may be different depending on the place where they reside. We ask ourselves whether teachers in rural areas are sufficiently prepared to carry out this communication through digital media. Thus, this study had as its aims to: (1) ascertain teachers’ digital competence self-assessment about the utilisation of ICT resources to communicate with other teachers, students and families, according to gender, type of school, age and years of teaching experience; (2) analyse comparatively if significant differences exist in terms of digital competence level between the internal categories of each variable; (3) identify which digital resources are significant predictors. A non-experimental design was used with 847 rural teachers from different rural areas in Spain. The results showed an integrating attitude of every teacher-expert in their digital skills, regarding communication both with students and their families and with the other colleagues at the educational centre. We found differences in teachers’ scores when comparing by gender and type of centre. Furthermore, we checked those applications such as Blogs, TikTok, Twitter and Moodle served were relevant predictors.
Keywords: Educación rural; Profesores - Formación profesional; Alfabetización digital; Teachers; Rural education; Educational technology; Computer literacy